PENTINGNYA STOCK OPNAME KOLEKSI PERPUSTAKAAN IPDN KAMPUS JAKARTA - BOGA PRATALA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2021)
This research discusses about stock opname collection at IPDN Kampus Jakarta. The purpose of this study was determining the advantages and disadvantages of stock opname collections. This activity uses a qualitative method in the form of case study. Data collection was conducted by the observation, interview, documentation. There were three informants in this study, namely the principal, teacher, and library staff. The results of this study indicate that the librarian of IPDN Kampus Jakarta did stock opname with the method of list / registration containing the parent number. The advantage of this research is knowing the condition of library materials in order to take eradication measures for collections that are not feasible, so that the development of collections can be done, making it easier to find library materials. On the other hand, it requires a short amount of data collection time, people cannot borrow collections during the activity. It can be concluded that stock opname library collection of IPDN Kampus Jakarta just use the register/ registration method containing the parent number. By doing this stock opname of IPDN Kampus Jakarta, the real collection of library could be found out. ABSTRAKPenelitian ini membahas tentang stock opname di Kampus IPDN Jakarta. Tujuan dari penelitian ini adalah untuk mengetahui kelebihan dan kekurangan dari koleksi stock opname. Kegiatan ini menggunakan metode kualitatif berupa studi kasus. Pengumpulan data dilakukan dengan observasi, wawancara, dokumentasi. Ada tiga informan dalam penelitian ini, yaitu kepala sekolah, guru, dan staf perpustakaan. Hasil penelitian ini menunjukkan bahwa perpustakaan Kampus IPDN Jakarta melakukan stock opname dengan metode daftar/registrasi berisi nomor induk. Manfaat dari penelitian ini adalah mengetahui kondisi bahan pustaka agar dapat dilakukan tindakan pemberantasan terhadap koleksi yang tidak layak, sehingga dapat dilakukan pengembangan koleksi, sehingga memudahkan dalam mencari bahan pustaka. Di sisi lain, membutuhkan waktu pengumpulan data yang singkat, orang tidak dapat meminjam koleksi selama kegiatan. Dapat disimpulkan bahwa stock opname koleksi perpustakaan Kampus IPDN Jakarta hanya menggunakan metode register/registrasi yang memuat nomor induk. Dengan melakukan stock opname Kampus IPDN Jakarta ini, dapat diketahui koleksi perpustakaan yang sebenarnya.